1984
DOI: 10.1126/science.6701524
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Deficiency and Hypertension: Correlation Between Magnesium-Deficient Diets and Microcirculatory Changes in Situ

Abstract: Rats maintained for 12 weeks on diets moderately or more severely deficient in magnesium showed significant elevations in arterial blood pressure compared to control animals. Examination of the mesenteric microcirculation in situ revealed that dietary magnesium deficiency resulted in reduced capillary, postcapillary, and venular blood flow concomitant with reduced terminal arteriolar, precapillary sphincter, and venular lumen sizes. The greater the degree of dietary magnesium deficiency the greater the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
1
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(155 citation statements)
references
References 31 publications
4
149
1
1
Order By: Relevance
“…4,5,7,19 -21 Mg 2ϩ also modulates neuronal activity 6,7 but the precise mechanisms are still unknown. In the present study, we showed an Mg 2ϩ effect on sympathetic tone both in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7,19 -21 Mg 2ϩ also modulates neuronal activity 6,7 but the precise mechanisms are still unknown. In the present study, we showed an Mg 2ϩ effect on sympathetic tone both in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 On the contrary, Mg 2ϩ deficiency results in a high catecholamine level, altered barofunction, and hypertension. 6,7 Sympathoactivation and catecholamine elevation induce tachycardia, glucose intolerance, and abnormal fat metabolism, as well as direct cardiotoxicity. 8,9 At the same time, recent clinical studies revealed that Mg 2ϩ protects brain from ischemic damages.…”
mentioning
confidence: 99%
“…Mg 2ϩ deficiency results in small cell size and cell cycle arrest (11), as well as accelerated cell senescence (12), and intracellular Mg 2ϩ levels modulate the activity of many ion channels (13)(14)(15)(16)(17)(18). In whole animals, hypomagnesemia results in hypocalcemia (19,20), and Mg 2ϩ deficiency has been correlated to hypertension (21,22).…”
Section: Magnesium (Mgmentioning
confidence: 99%
“…Mg 2ϩ deficiency results in small cell size and cell cycle arrest (11), as well as accelerated cell senescence (12), and intracellular Mg 2ϩ levels modulate the activity of many ion channels (13-18). In whole animals, hypomagnesemia results in hypocalcemia (19,20), and Mg 2ϩ deficiency has been correlated to hypertension (21,22 (42)(43)(44)46), has raised interest in putative Mg 2ϩ channels. TRPM6 mutations have been linked to the human genetic disease familial hypomagnesemia with secondary hypocalcemia (47,48).…”
mentioning
confidence: 99%
“…Intracellular free magnesium concentration is low in clinical and experimental hypertension (Resnick et al, 1984;Ng et al, 1992). Magnesium deficiency in rats induces hypertension, reduces blood vessel lumen (Altura et al, 1984) and increases plasma endothelin concentration (Weglicki et al, 1992). Magnesium infusion induces vasodilatation (Ji et al, 1983), and recent studies report that it strongly inhibits endothelin-1-induced vasoconstriction (Kemp et al, 1993).…”
Section: Introductionmentioning
confidence: 99%